Antimicrobial Secondary Metabolites from the Mangrove Plants of Asia and the Pacific - Mazdida Sulaiman; Veeranoot Nissapatorn; Mohammed Rahmatullah; Alok K. Paul; Mogana Rajagopal; Nor Azizun Rusdi; Jaya Seelan Sathya Seelan; Monica Suleiman; Zainul Amiruddin Zakaria; Christophe Patrice Andie Wiart (MDPI, 2022)
Microbes such as the White Spot Syndrome Virus account for severe losses in the shrimp farming industry globally. This review examines the literature on the mangrove plants of Asia and the Pacific with antibacterial, antifungal, or antiviral activities. All of the available data published on this subject were collected from Google Scholar, PubMed, Science Direct, Web of Science, ChemSpider, PubChem, and a library search from 1968 to 2022. Out of about 286 plant species, 119 exhibited antimicrobial effects, and a total of 114 antimicrobial natural products have been identified including 12 with MIC values below 1 µg/mL. Most of these plants are medicinal. The mangrove plants of Asia and the Pacific yield secondary metabolites with the potential to mitigate infectious diseases in shrimp aquaculture.